2003
DOI: 10.1097/01.ccm.0000081438.04801.d9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of immune resolution

Abstract: Initially after injury, the innate/proinflammatory and some aspects of the acquired immune response are up-regulated to maintain a defense against foreign pathogens, clear tissue debris present at the wound site, and orchestrate aspects of tissue remodeling, cell proliferation and angiogenic process, associated with the wound response. However, for proper wound healing to progress, this initial inflammatory response has to be regulated or shut down so as to allow for the reestablishment of matrix, recellulariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 186 publications
0
30
0
5
Order By: Relevance
“…Animal studies have shown that septic mice with TGF-␤1 gene deletions develop spontaneous organ failure associated with infiltration of MNCs, which indicates that this gene may play a role in controlling inflammatory responses (16). In addition to its immunologic effects, TGF-␤1 is also known for its enhancing effect on fibrous tissue formation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that septic mice with TGF-␤1 gene deletions develop spontaneous organ failure associated with infiltration of MNCs, which indicates that this gene may play a role in controlling inflammatory responses (16). In addition to its immunologic effects, TGF-␤1 is also known for its enhancing effect on fibrous tissue formation (17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their phagocytic and killing properties, neutrophils synthesize numerous proinflammatory cytokines and chemokines that may amplify the inflammatory process (5)(6)(7)(8)(9). Furthermore, recent studies have shown that neutrophil apoptosis is delayed in patients with sepsis, ALI, and BPD (10)(11)(12). Expression of many of these proinflammatory and antiapoptotic genes is regulated at the level of transcription by the transcription factor NFκB (13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Following the recognition of a pathogen, APC and lymphocytes are activated leading to the production of pro-inflammatory cytokines, processes that are tightly controlled as a local inflammatory process under normal circumstances. Uncontrolled or amplified inflammation can lead to septic shock and damage to host tissue [38]. In the steady state DC in the intestine, under the conditioning of intestinal epithelium, predominantly induce TH2-type response to avoid pathological inflammatory response.…”
Section: Discussionmentioning
confidence: 99%